Myopia and daylight—A combination of factors - Hobday, Richard; Aarts, Mariëlle; Cajochen, Christian; Maierova, Lenka; Münch, Mirjam; Osterhaus, Werner; Stefani, Oliver; Wulff, Katharina (Frontiers in Medicine, 2025)
The incidence of myopia among school children has risen markedly over the last three decades. In urban areas of South and East Asia, as many as 80–90% of young adults are now myopic. This trend is occurring elsewhere around the world. During the COVID-19 lockdowns, children in many countries were confined indoors and spent an undue amount of time exposed to television screens, computers, and mobile devices. This resulted in an acceleration in the incidence and progression of the condition. Myopia is a significant public health issue as it is a leading cause of blindness and other vision problems. Yet the underlying mechanisms that produce the condition remain elusive. Pseudomyopia has recently been proposed as an independent risk factor for myopia. We hypothesize that pseudomyopia induced by prolonged close work, stress, and anxiety combines and is further amplified by chronically low ambient light levels. If time spent outdoors in daylight is restricted, the effects worsen and together may play a significant part in myopia epidemics.